Approaches to managing logistics processes under digital economy - N. S. Seliverstova; R. A. Sabitov; G. S. Smirnova (Russian Journal of Economics and Law)
Objective: to review the main management models and approaches to the study of logistics processes in production ecosystems.Methods: abstract-logical, dialectical, phenomenological methods.Results: the main directions and methods of research in the field of digitalization of logistics processes are described; the accelerated growth of e-commerce and force majeure factors (epidemic, a complex of geopolitical factors) are identified as a driver for the development of solutions in the field of improving the efficiency of logistics processes in the Russian economy; promising directions for the development of logistics process management models are identified.Scientific novelty: it is shown that the directions of foreign authors’ research in the field of logistics are broader, while Russian researchers have a significant potential to search for new technological and methodological solutions in this area; the relevance of the research development in the field of logistics processes digitalization is shown, including that on the basis of predictive analysis models.Practical significance: the understanding of problems in the field of logistics, revealed in the work, makes it urgent to develop a set of projects in this area to increase the efficiency of existing digital ecosystems, and also creates a basis for further research in this area.